The map that leads to you - Monninger, Joseph (St. Martin's Press, 2017)
"A romantic, vivid novel that takes place in the tender time of a young woman's life: Heather has graduated from college and is traveling around Europe with her two best friends. She's left school responsibility behind and adult responsibility is looming, but this is her one, ONE last summer to be free. Heather doesn't expect to even meet Jack, let alone fall in love with him. Jack is an enigmatic Vermonter a few years older than she is, who is following his grandfather's journal to various cities around Europe. But in the same way that forces are bringing Jack and Heather together, life and duty are pushing them apart. And Jack has a secret that is going to change absolutely everything"--